RETRACTED: 3D-Method for Determining the Imaging Quality of Ultrasound Probes - Fröhlich, Eckhart; Satrapa, Jaroslav; Schmidt, Tatjana; Malek, Nisar; Joseph Gilot, Bryant; Debove, Ines; Pauluschke-Fröhlich, Jan (Journal of Medical Informatics and Decision Making, 2015)
Background: Monitoring ultrasonic probe quality remains an important problem which impacts diagnostic accuracy. Here we present a quantitative method to assess probe quality primarily based on measuring probe maximum contrast (dB) and dynamic range. Method: Contrast relevant parameters of 26 transducer models manufactured by five manufacturers were measured with a novel Random Void Phantom (RVP) approach. 3D-data were acquired and analysed to determine image quality. Results: Acoustic contrast values ranging from 15dB to 36dB were observed. Conclusion: By examining artefact producing side lobes, the novel RVP approach presented here permits a quantitative assessment of ultrasound probe quality.
Keywords: Ultrasonic image quality; random void phantom; side lobes; acoustic contrast